Monetary theory and monetary policy in the 1970s : proceedings of the 1970 Sheffield Money Seminar - Clayton, George; Gilbert, J. C.; Sedgwick, Robert (London : Oxford University Press, 1971)
This book contains the papers and proceedings of the Sheffield Seminar on Monetary theory and monetary policy in the 1970s, held in September 1970. The idea of the seminar was to provide a forum for contributions to monetary theory and its policy implications, including lines for future development.
Errata slip inserted. Includes index
Includes bibliographical references.
usc 9/11/17; 12/2/18
Loans
Keywords: Money; Monetary policy; Great Britain